Patterns of antibiotic resistance genes and virulence factor genes in the gut microbiome of patients with osteoarthritis and rheumatoid arthritis - Guo, Yaqi; Feng, Hang; Du, Lin; Yu, Zhenghong (Frontiers in Microbiology, 2024)
BackgroundThe gut microbiome compositions of osteoarthritis (OA) and rheumatoid arthritis (RA) patients have been revealed; however, the functional genomics, particularly antibiotic resistance genes (ARGs) and virulence factor genes (VFGs), have not yet been explored.MethodsWe used gut metagenomic data to elucidate the distribution of ARGs and VFGs. Building on these differences in gut microbiome, we developed a diagnostic model using a random forest classifier based on ARG and VFG abundances.ResultsOur results indicated that both OA and RA patients exhibit significantly higher alpha diversity in ARGs, as measured by observed genes, the Shannon index, and the Simpson index, compared to healthy controls. However, this increased diversity is not significantly different between OA and RA patients. In contrast, VFGs showed higher diversity in RA patients than in healthy individuals, which was not as pronounced in OA patients. An analysis of the top 20 ARGs and VFGs revealed a largely similar composition between the three groups, with notable exceptions of certain genes that were uniquely enriched in either OA or RA patients. This suggests unique microbial patterns associated with each condition. Our beta diversity analysis further demonstrated distinct distributions of ARG and VFG profiles across the three groups, with several genes significantly enriched in both OA and RA patients, indicating potential markers for these diseases. The model achieved high accuracy (74.7–83.6%) when distinguishing both OA and RA from healthy controls using ARG profiles and substantial accuracy using VFG profiles.ConclusionThese results support the potential of ARGs and VFGs as reliable biomarkers for diagnosing OA and RA.